Pentingnya Nilai Persatuan Perpektif Al-Quran Surah Al-Imran Ayat 103 dalam Mengatasi Pandemi Covid-19 - Mukhtar (Islamic Religious Education Departement, 2021)
The values ​​and spirit of unity and the prohibition of division have long existed and are taught by Islam, as in Surah Al Imran verse 103. Based on the interpretation of Ibn Kasir, Al Misbah, and Al Qurtubi, it explains the importance of unity so that there is a